2018
DOI: 10.1055/a-0777-2420
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Lobaric Acid via Suppressing NF-κB/MAPK Pathways or NLRP3 Inflammasome Activation

Abstract: Lobaric acid (LA) is a constituent of the lichen Stereocaulon alpinum. LA has multiple biological activities, including antibacterial and antioxidant ones. The purpose of this study was to investigate the effect of LA and its mechanism on lipopolysaccharide (LPS)-induced inflammatory responses in macrophages. Macrophages were pretreated with different concentrations of LA (0.2 – 20 µM), followed by LPS stimulation. LA treatment of LPS stimulated macrophages decreased their nitric oxide production and the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…[30 -31,35 -38] Lobaric acid from Stereocaulon alpinum influences lipopolysaccharide (LPS)-induced inflammatory responses in macrophages. [38] Furthermore, P. hypoleucinum, R. phycopsis, and X. parietina are promising lichens that have previously exhibited therapeutic proprieties. [29,[39][40] Coassini-Lokar et al [29] demonstrated that P. hypoleucinum has a high concentration in usnic, norstictic, and hypostictic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30 -31,35 -38] Lobaric acid from Stereocaulon alpinum influences lipopolysaccharide (LPS)-induced inflammatory responses in macrophages. [38] Furthermore, P. hypoleucinum, R. phycopsis, and X. parietina are promising lichens that have previously exhibited therapeutic proprieties. [29,[39][40] Coassini-Lokar et al [29] demonstrated that P. hypoleucinum has a high concentration in usnic, norstictic, and hypostictic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the isolated compounds (+)‐iso‐usnic acid and atranorin, methyl orsellinate, and parietin have an inhibitory activity on the production of inflammatory factors, including NO, in LPS‐stimulated macrophages. Several studies have explored the anti‐inflammatory of various lichens compounds such as lobaric acid, usnic acid, atranorin, and atraric acid [30–31,35–38] …”
Section: Discussionmentioning
confidence: 99%
“…Notably, various factors and molecules are capable of initiating the priming signals for the activation of the NLRP3 inflammasome in LPS-primed macrophages (8,9,12). Among them, MAPK is a potent activator of the priming signal of the NLRP3 inflammasome (49). As shown in Fig.…”
Section: Tris Dba Reduced Mitochondrial Ros Production In Bmdmsmentioning
confidence: 99%
“…Autophagy/NLRP3 inflammasome axis. Notably, autophagy can inhibit the priming and activation signals of the NLRP3 inflammasome (26,44,45,49). We thus evaluated whether Tris DBA could regulate the autophagy/NLRP3 inflammasome axis to render its therapeutic effects on ASLN mice.…”
Section: Tris Dba Reduced Mitochondrial Ros Production In Bmdmsmentioning
confidence: 99%
“…Predominantly expressed P2X7R in various types of macrophages participated in immune responses and inflammatory diseases [98]. Predominantly expressed P2X7R in various types of macrophages participated in immune responses and inflammatory diseases [99].…”
Section: Active Ingredients Of Tcms For Inflammation-related Diseases Management Via P2x4r and P2x7rmentioning
confidence: 99%